Thermomechanical postbuckling of thick FGM plates resting on elastic foundations with tangential edge constraints - Tung, Hoang Van (Vietnam Journal of Mechanics, 2016)
This paper investigates the effects of tangential edge  constraints and elastic foundations on the buckling and postbuckling  behavior of thick FGM rectangular plates resting on elastic foundations and  subjected to thermal and thermomechanical loading conditions. Material  properties are assumed to be temperature dependent, and graded in the  thickness direction according to a simple power law distribution in terms of  the volume fractions of constituents. Governing equations are based on the higher order shear deformation plate theory incorporating the von Karman  geometrical nonlinearity, initial geometrical imperfection, tangential edge  constraints and Pasternak type elastic foundations. Approximate solutions  are assumed to satisfy simply supported boundary conditions and Galerkin  procedure is applied to derive expressions of buckling loads and  load-deflection relations. In thermal postbuckling analysis, an iteration  algorithm is employed to determine critical buckling temperatures and  postbuckling temperature-deflection equilibrium paths. The separate and  simultaneous effects of tangential edge restraints, elastic foundations and  temperature dependence of material properties on the buckling and  postbuckling responses of higher order shear deformable FGM plates are  analyzed and discussed.